Moulding lives, shaping destinies : motherhood and nation in celestial bodies by Jokha Alharthi and a golden age by Tahmima Anam - Rabiatul Adawiyah Yusoff,; Raihanah M.M., (Penerbit Universiti Kebangsaan Malaysia, 2022)
Female narratives hold an important place in literature as they tell stories from women’s perspectives, spatially and temporally. In Celestial Bodies by Jokha Alharthi and A Golden Age by Tahmima Anam, the female characters play a significant role in determining the outcome of the story as their personal narratives run parallel to the history of Oman and Bangladesh in the 1970s, respectively. The paper examines the intersectionality of gendered narratives through the lens of motherhood and individual lives within a nation in both texts with the aim of uncovering its manifestation in both Omani and Bangladeshi societies. The methodology adopts the theory of parenting as a lens to examine the textual depiction of mothering within the two socio-cultural contexts of Oman and Bangladesh with a specific focus on Diana Baumrind’s categorisation of parenting styles. The findings suggest that the mothering styles portrayed in the two novels, namely authoritarian and permissive, are present in two distinct yet overlapping manners: one, within mother-daughter relationships grounded in cultural engagement, and two, through participation in nationhood. In addition, mothers in Celestial Bodies serve as witnesses to the cultural changes in Oman, creating intra-gender generational conflicts. In contrast, the mother figure in A Golden Age functions as the backbone of the youth’s participation in Bangladeshi liberation. Many of the choices made by the mothers in the two novels implicate the lives of the youth, society, and consequently the nation-states. The implication of this comparative reading shows that the mothering roles in women’s fiction are rich and multi-faceted as they partake in the pursuit of nationhood within and without the family institution.